Carbon Nanofibers Modified with Heteroatoms as Metal‐Free Catalysts for the Oxidative Dehydrogenation of Propane. Issue 9 (19th August 2014) - Marco, Yanila; Roldán, Laura; Muñoz, Edgar; García‐Bordejé, Enrique
Abstract Carbon nanofibres (CNFs) were modified with B and P by an ex situ approach. In addition, CNFs doped with N were prepared in situ using ethylenediamine as the N and C source. After calcination, the doped CNFs were used as catalysts for the oxidative dehydrogenation of propane. For B‐CNFs, the effects of boron loading and calcination temperature on B speciation and catalytic conversion were studied. For the same reaction temperatures and conversions, B‐ and P‐doped CNFs exhibited higher selectivities to propene than pristine CNFs. The N‐CNFs were the most active but the least selective of the catalysts tested here. Our results also show that the type of P precursor affects the selectivity to propene and that CNFs modified using triphenylphosphine as the precursor provided the highest selectivity at isoconversion.